Barriers to disability-inclusive disaster management in the Solomon Islands: Perspectives of people with disability. (March 2019) - King, Julie; Edwards, Nicole; Watling, Hanna; Hair, Sara
Abstract: There is growing emphasis on disability-inclusive disaster management within key international guidance on disaster management. Yet, people with disability (PWD) are routinely excluded from the disaster management cycle and ignored or forgotten during all phases. This study explored barriers to inclusive disaster management through in-depth interviews with nine PWD and two carers of PWD from the Solomon Islands in 2015. Findings indicate PWD in the Solomon Islands are invisible in disasters. Failure to involve PWD can be linked to stigma, discrimination and the hidden nature of some disabilities. Government and aid organisations had a poor understanding of disability-specific needs in disasters and PWD had received no information on how to manage during or post disasters. Negative societal views of PWD perpetuated exclusion; based on notions that they are unable to actively contribute. Unequal access to resources, failure to adapt the built environment, and poor housing are problems PWD heightened the vulnerability of PWD in disasters. Raising awareness, combatting negative attitudes, and addressing discrimination would reduce vulnerability and result in better outcomes during disasters for all people in the Solomon Islands, inclusive of PWD. Findings of the research are relevant for PWD, not only in the Global South, but also in the Global North.